Usable security in Electronic Health Record System: A review on the Saudi Arabian perspective (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Background and objective:The electronic health record (EHR) is the fundamental buildingblock of digital healthcare. With the increase of sensitive personal data stored in the EHR, theusability of the system and information security become important concerns. Experts areconstantly developing techniques to improve security while maintaining usability. This iswhere usable security comes into play. More specifically, it is the prevention of unauthorizedaccess while maintaining simplicity for the user. This review paper analyses the availableevidence on security and usability of healthcare software to derive recommendations for theSaudi healthcare sector.Method:A review of the current literature was conducted usingPubMed, Google Scholar, and the results were analysed.Results:Healthcare professionalswork under time pressure and with limited resources. They need efficient and usable digitaltools that include security measures. Lack of certainty undermines information security andultimately compromises patient safety. There are no clear global guidelines for usable securityin healthcare. Usability research in other fields suggests that such research would need to bespecific to a country or a region with shared cultural and linguistic traits.Conclusion:The influence of usability in health care, and EHR security in particular,shouldbe empirically investigated in a Saudi Arabian context in future studies.